I never complain in real life. Krystyna Sienkiewicz - Kilian, Marlena (Difficult situation in biographies: Volume 9, 2025)
Krystyna Sienkiewicz (1935–2017) is a popular Polish artist known to a wider audience mainly for her film and stage work, which she successfully continued despite serious health and functional difficulties. This text analyzes the strategies she undertook to adapt to her acquired disability. The resulting case study was carried out in two stages: the first focused on the artist’s functional limitations resulting from the loss of vision, the second – conducted 25 years later, on the deepening visual impairment, but also additionally: motor, speech and cognitive functions. The current study is an update of the first study and provides a comparison of the artist’s functional state at the age of 65 and 82. The research was based on material obtained through direct, open and free observation of the artist in home and stage conditions, also from interviews conducted with her and household members, and also from the analysis of interviews and press articles, supported by the analysis of medical documentation, as well as the artist’s musical, film, stage and writing achievements and her visual art products. The research showed that Krystyna Sienkiewicz was able to eliminate the functional consequences of vision damage at an early and later stage of her life by using highly developed adaptive strategies, including self-rehabilitation. In the process of convalescence after her illness, she regained a high level of life activity and social participation, continuing her extensive charity work and, until the end of her life, also earning money. The worsening deterioration of her health (broken arm, oncological disease, stroke) did not lead to her life deactivation, on the contrary, it motivated her to undertake a creative adaptation effort. She focused on creating a friendly home and work environment, along with an extensive network of mutual support. She found an antidote to the hardships of life in the broadly understood artistic creativity. Until the end of her life she remained a person full of humor, intellectually agile and independent in life.